Adequacy: Adequacy of denotational semantics with respect to operational semantics
module plfa.part3.Adequacy where
Introduction
Having proved a preservation property in the last chapter, a natural next step would be to prove progress. That is, to prove a property of the form
If γ ⊢ M ↓ v, then either M is a lambda abstraction or M —→ N for some N.
Such a property would tell us that having a denotation implies either reduction to normal form or divergence. This is indeed true, but we can prove a much stronger property! In fact, having a denotation that is a function value (not ⊥
) implies reduction to a lambda abstraction.
This stronger property, reformulated a bit, is known as adequacy. That is, if a term M
is denotationally equal to a lambda abstraction, then M
reduces to a lambda abstraction.
ℰ M ≃ ℰ (ƛ N) implies M —↠ ƛ N' for some N'
Recall that ℰ M ≃ ℰ (ƛ N)
is equivalent to saying that γ ⊢ M ↓ (v ↦ w)
for some v
and w
. We will show that γ ⊢ M ↓ (v ↦ w)
implies multi-step reduction a lambda abstraction. The recursive structure of the derivations for γ ⊢ M ↓ (v ↦ w)
are completely different from the structure of multi-step reductions, so a direct proof would be challenging. However, The structure of γ ⊢ M ↓ (v ↦ w)
closer to that of BigStep call-by-name evaluation. Further, we already proved that big-step evaluation implies multi-step reduction to a lambda (cbn→reduce
). So we shall prove that γ ⊢ M ↓ (v ↦ w)
implies that γ' ⊢ M ⇓ c
, where c
is a closure (a term paired with an environment), γ'
is an environment that maps variables to closures, and γ
and γ'
are appropriate related. The proof will be an induction on the derivation of γ ⊢ M ↓ v
, and to strengthen the induction hypothesis, we will relate semantic values to closures using a logical relation 𝕍
.
The rest of this chapter is organized as follows.
To make the
𝕍
relation down-closed with respect to⊑
, we must loosen the requirement thatM
result in a function value and instead require thatM
result in a value that is greater than or equal to a function value. We establish several properties about being ``greater than a function’’.We define the logical relation
𝕍
that relates values and closures, and extend it to a relation on terms𝔼
and environments𝔾
. We prove several lemmas that culminate in the property that if𝕍 v c
andv′ ⊑ v
, then𝕍 v′ c
.We prove the main lemma, that if
𝔾 γ γ'
andγ ⊢ M ↓ v
, then𝔼 v (clos M γ')
.We prove adequacy as a corollary to the main lemma.
Imports
open import Relation.Binary.PropositionalEquality using (_≡_; refl) open import Data.Product.Base using (_×_; Σ; Σ-syntax; ∃; ∃-syntax; proj₁; proj₂) renaming (_,_ to ⟨_,_⟩) open import Data.Sum.Base using (_⊎_; inj₁; inj₂) open import Relation.Nullary.Negation using (¬_; contradiction) open import Data.Empty using () renaming (⊥ to Bot) open import Data.Unit.Base using (tt; ⊤) open import Relation.Nullary.Decidable using (Dec; yes; no) open import Function.Base using (_∘_) open import plfa.part2.Untyped using (Context; _⊢_; ★; _∋_; ∅; _,_; Z; S_; `_; ƛ_; _·_; rename; subst; ext; exts; _[_]; subst-zero; _—↠_; _—→⟨_⟩_; _∎; _—→_; ξ₁; ξ₂; β; ζ) open import plfa.part2.Substitution using (ids; sub-id) open import plfa.part2.BigStep using (Clos; clos; ClosEnv; ∅'; _,'_; _⊢_⇓_; ⇓-var; ⇓-lam; ⇓-app; ⇓-determ; cbn→reduce) open import plfa.part3.Denotational using (Value; Env; `∅; _`,_; _↦_; _⊑_; _⊢_↓_; ⊥; all-funs∈; _⊔_; ∈→⊑; var; ↦-elim; ↦-intro; ⊔-intro; ⊥-intro; sub; ℰ; _≃_; _iff_; ⊑-trans; ⊑-conj-R1; ⊑-conj-R2; ⊑-conj-L; ⊑-refl; ⊑-fun; ⊑-bot; ⊑-dist; sub-inv-fun) open import plfa.part3.Soundness using (soundness)
The property of being greater or equal to a function
We define the following short-hand for saying that a value is greater-than or equal to a function value.
above-fun : Value → Set above-fun u = Σ[ v ∈ Value ] Σ[ w ∈ Value ] v ↦ w ⊑ u
If a value u
is greater than a function, then an even greater value u'
is too.
above-fun-⊑ : ∀{u u' : Value} → above-fun u → u ⊑ u' ------------------- → above-fun u' above-fun-⊑ ⟨ v , ⟨ w , lt' ⟩ ⟩ lt = ⟨ v , ⟨ w , ⊑-trans lt' lt ⟩ ⟩
The bottom value ⊥
is not greater than a function.
above-fun⊥ : ¬ above-fun ⊥ above-fun⊥ ⟨ v , ⟨ w , lt ⟩ ⟩ with sub-inv-fun lt ... | ⟨ Γ , ⟨ f , ⟨ Γ⊆⊥ , ⟨ lt1 , lt2 ⟩ ⟩ ⟩ ⟩ with all-funs∈ f ... | ⟨ A , ⟨ B , m ⟩ ⟩ with Γ⊆⊥ m ... | ()
If the join of two values u
and u'
is greater than a function, then at least one of them is too.
above-fun-⊔ : ∀{u u'} → above-fun (u ⊔ u') → above-fun u ⊎ above-fun u' above-fun-⊔{u}{u'} ⟨ v , ⟨ w , v↦w⊑u⊔u' ⟩ ⟩ with sub-inv-fun v↦w⊑u⊔u' ... | ⟨ Γ , ⟨ f , ⟨ Γ⊆u⊔u' , ⟨ lt1 , lt2 ⟩ ⟩ ⟩ ⟩ with all-funs∈ f ... | ⟨ A , ⟨ B , m ⟩ ⟩ with Γ⊆u⊔u' m ... | inj₁ x = inj₁ ⟨ A , ⟨ B , (∈→⊑ x) ⟩ ⟩ ... | inj₂ x = inj₂ ⟨ A , ⟨ B , (∈→⊑ x) ⟩ ⟩
On the other hand, if neither of u
and u'
is greater than a function, then their join is also not greater than a function.
not-above-fun-⊔ : ∀{u u' : Value} → ¬ above-fun u → ¬ above-fun u' → ¬ above-fun (u ⊔ u') not-above-fun-⊔ naf1 naf2 af12 with above-fun-⊔ af12 ... | inj₁ af1 = contradiction af1 naf1 ... | inj₂ af2 = contradiction af2 naf2
The converse is also true. If the join of two values is not above a function, then neither of them is individually.
not-above-fun-⊔-inv : ∀{u u' : Value} → ¬ above-fun (u ⊔ u') → ¬ above-fun u × ¬ above-fun u' not-above-fun-⊔-inv af = ⟨ f af , g af ⟩ where f : ∀{u u' : Value} → ¬ above-fun (u ⊔ u') → ¬ above-fun u f{u}{u'} af12 ⟨ v , ⟨ w , lt ⟩ ⟩ = contradiction ⟨ v , ⟨ w , ⊑-conj-R1 lt ⟩ ⟩ af12 g : ∀{u u' : Value} → ¬ above-fun (u ⊔ u') → ¬ above-fun u' g{u}{u'} af12 ⟨ v , ⟨ w , lt ⟩ ⟩ = contradiction ⟨ v , ⟨ w , ⊑-conj-R2 lt ⟩ ⟩ af12
The property of being greater than a function value is decidable, as exhibited by the following function.
above-fun? : (v : Value) → Dec (above-fun v) above-fun? ⊥ = no above-fun⊥ above-fun? (v ↦ w) = yes ⟨ v , ⟨ w , ⊑-refl ⟩ ⟩ above-fun? (u ⊔ u') with above-fun? u | above-fun? u' ... | yes ⟨ v , ⟨ w , lt ⟩ ⟩ | _ = yes ⟨ v , ⟨ w , (⊑-conj-R1 lt) ⟩ ⟩ ... | no _ | yes ⟨ v , ⟨ w , lt ⟩ ⟩ = yes ⟨ v , ⟨ w , (⊑-conj-R2 lt) ⟩ ⟩ ... | no x | no y = no (not-above-fun-⊔ x y)
Relating values to closures
Next we relate semantic values to closures. The relation 𝕍
is for closures whose term is a lambda abstraction, i.e., in weak-head normal form (WHNF). The relation 𝔼 is for any closure. Roughly speaking, 𝔼 v c
will hold if, when v
is greater than a function value, c
evaluates to a closure c'
in WHNF and 𝕍 v c'
. Regarding 𝕍 v c
, it will hold when c
is in WHNF, and if v
is a function, the body of c
evaluates according to v
.
𝕍 : Value → Clos → Set 𝔼 : Value → Clos → Set
We define 𝕍
as a function from values and closures to Set
and not as a data type because it is mutually recursive with 𝔼
in a negative position (to the left of an implication). We first perform case analysis on the term in the closure. If the term is a variable or application, then 𝕍
is false (Bot
). If the term is a lambda abstraction, we define 𝕍
by recursion on the value, which we describe below.
𝕍 v (clos (` x₁) γ) = Bot 𝕍 v (clos (M · M₁) γ) = Bot 𝕍 ⊥ (clos (ƛ M) γ) = ⊤ 𝕍 (v ↦ w) (clos (ƛ N) γ) = (∀{c : Clos} → 𝔼 v c → above-fun w → Σ[ c' ∈ Clos ] (γ ,' c) ⊢ N ⇓ c' × 𝕍 w c') 𝕍 (u ⊔ v) (clos (ƛ N) γ) = 𝕍 u (clos (ƛ N) γ) × 𝕍 v (clos (ƛ N) γ)
If the value is
⊥
, then the result is true (⊤
).If the value is a join (u ⊔ v), then the result is the pair (conjunction) of 𝕍 is true for both u and v.
The important case is for a function value
v ↦ w
and closureclos (ƛ N) γ
. Given any closurec
such that𝔼 v c
, ifw
is greater than a function, thenN
evaluates (withγ
extended withc
) to some closurec'
and we have𝕍 w c'
.
The definition of 𝔼
is straightforward. If v
is a greater than a function, then M
evaluates to a closure related to v
.
𝔼 v (clos M γ') = above-fun v → Σ[ c ∈ Clos ] γ' ⊢ M ⇓ c × 𝕍 v c
The proof of the main lemma is by induction on γ ⊢ M ↓ v
, so it goes underneath lambda abstractions and must therefore reason about open terms (terms with variables). So we must relate environments of semantic values to environments of closures. In the following, 𝔾
relates γ
to γ'
if the corresponding values and closures are related by 𝔼
.
𝔾 : ∀{Γ} → Env Γ → ClosEnv Γ → Set 𝔾 {Γ} γ γ' = ∀{x : Γ ∋ ★} → 𝔼 (γ x) (γ' x) 𝔾-∅ : 𝔾 `∅ ∅' 𝔾-∅ {()} 𝔾-ext : ∀{Γ}{γ : Env Γ}{γ' : ClosEnv Γ}{v c} → 𝔾 γ γ' → 𝔼 v c → 𝔾 (γ `, v) (γ' ,' c) 𝔾-ext {Γ} {γ} {γ'} g e {Z} = e 𝔾-ext {Γ} {γ} {γ'} g e {S x} = g
We need a few properties of the 𝕍
and 𝔼
relations. The first is that a closure in the 𝕍
relation must be in weak-head normal form. We define WHNF has follows.
data WHNF : ∀ {Γ A} → Γ ⊢ A → Set where ƛ_ : ∀ {Γ} {N : Γ , ★ ⊢ ★} → WHNF (ƛ N)
The proof goes by cases on the term in the closure.
𝕍→WHNF : ∀{Γ}{γ : ClosEnv Γ}{M : Γ ⊢ ★}{v} → 𝕍 v (clos M γ) → WHNF M 𝕍→WHNF {M = ` x} {v} () 𝕍→WHNF {M = ƛ N} {v} vc = ƛ_ 𝕍→WHNF {M = L · M} {v} ()
Next we have an introduction rule for 𝕍
that mimics the ⊔-intro
rule. If both u
and v
are related to a closure c
, then their join is too.
𝕍⊔-intro : ∀{c u v} → 𝕍 u c → 𝕍 v c --------------- → 𝕍 (u ⊔ v) c 𝕍⊔-intro {clos (` x) γ} () vc 𝕍⊔-intro {clos (ƛ N) γ} uc vc = ⟨ uc , vc ⟩ 𝕍⊔-intro {clos (L · M) γ} () vc
In a moment we prove that 𝕍
is preserved when going from a greater value to a lesser value: if 𝕍 v c
and v' ⊑ v
, then 𝕍 v' c
. This property, named sub-𝕍
, is needed by the main lemma in the case for the sub
rule.
To prove sub-𝕍
, we in turn need the following property concerning values that are not greater than a function, that is, values that are equivalent to ⊥
. In such cases, 𝕍 v (clos (ƛ N) γ')
is trivially true.
not-above-fun-𝕍 : ∀{v : Value}{Γ}{γ' : ClosEnv Γ}{N : Γ , ★ ⊢ ★ } → ¬ above-fun v ------------------- → 𝕍 v (clos (ƛ N) γ') not-above-fun-𝕍 {⊥} af = tt not-above-fun-𝕍 {v ↦ v'} af = contradiction ⟨ v , ⟨ v' , ⊑-refl ⟩ ⟩ af not-above-fun-𝕍 {v₁ ⊔ v₂} af with not-above-fun-⊔-inv af ... | ⟨ af1 , af2 ⟩ = ⟨ not-above-fun-𝕍 af1 , not-above-fun-𝕍 af2 ⟩
The proofs of sub-𝕍
and sub-𝔼
are intertwined.
sub-𝕍 : ∀{c : Clos}{v v'} → 𝕍 v c → v' ⊑ v → 𝕍 v' c sub-𝔼 : ∀{c : Clos}{v v'} → 𝔼 v c → v' ⊑ v → 𝔼 v' c
We prove sub-𝕍
by case analysis on the closure’s term, to dispatch the cases for variables and application. We then proceed by induction on v' ⊑ v
. We describe each case below.
sub-𝕍 {clos (` x) γ} {v} () lt sub-𝕍 {clos (L · M) γ} () lt sub-𝕍 {clos (ƛ N) γ} vc ⊑-bot = tt sub-𝕍 {clos (ƛ N) γ} vc (⊑-conj-L lt1 lt2) = ⟨ (sub-𝕍 vc lt1) , sub-𝕍 vc lt2 ⟩ sub-𝕍 {clos (ƛ N) γ} ⟨ vv1 , vv2 ⟩ (⊑-conj-R1 lt) = sub-𝕍 vv1 lt sub-𝕍 {clos (ƛ N) γ} ⟨ vv1 , vv2 ⟩ (⊑-conj-R2 lt) = sub-𝕍 vv2 lt sub-𝕍 {clos (ƛ N) γ} vc (⊑-trans{v = v₂} lt1 lt2) = sub-𝕍 (sub-𝕍 vc lt2) lt1 sub-𝕍 {clos (ƛ N) γ} vc (⊑-fun lt1 lt2) ev1 sf with vc (sub-𝔼 ev1 lt1) (above-fun-⊑ sf lt2) ... | ⟨ c , ⟨ Nc , v4 ⟩ ⟩ = ⟨ c , ⟨ Nc , sub-𝕍 v4 lt2 ⟩ ⟩ sub-𝕍 {clos (ƛ N) γ} {v ↦ w ⊔ v ↦ w'} ⟨ vcw , vcw' ⟩ ⊑-dist ev1c sf with above-fun? w | above-fun? w' ... | yes af2 | yes af3 with vcw ev1c af2 | vcw' ev1c af3 ... | ⟨ clos L δ , ⟨ L⇓c₂ , 𝕍w ⟩ ⟩ | ⟨ c₃ , ⟨ L⇓c₃ , 𝕍w' ⟩ ⟩ rewrite ⇓-determ L⇓c₃ L⇓c₂ with 𝕍→WHNF 𝕍w ... | ƛ_ = ⟨ clos L δ , ⟨ L⇓c₂ , ⟨ 𝕍w , 𝕍w' ⟩ ⟩ ⟩ sub-𝕍 {c} {v ↦ w ⊔ v ↦ w'} ⟨ vcw , vcw' ⟩ ⊑-dist ev1c sf | yes af2 | no naf3 with vcw ev1c af2 ... | ⟨ clos {Γ'} L γ₁ , ⟨ L⇓c2 , 𝕍w ⟩ ⟩ with 𝕍→WHNF 𝕍w ... | ƛ_ {N = N'} = let 𝕍w' = not-above-fun-𝕍{w'}{Γ'}{γ₁}{N'} naf3 in ⟨ clos (ƛ N') γ₁ , ⟨ L⇓c2 , 𝕍⊔-intro 𝕍w 𝕍w' ⟩ ⟩ sub-𝕍 {c} {v ↦ w ⊔ v ↦ w'} ⟨ vcw , vcw' ⟩ ⊑-dist ev1c sf | no naf2 | yes af3 with vcw' ev1c af3 ... | ⟨ clos {Γ'} L γ₁ , ⟨ L⇓c3 , 𝕍w'c ⟩ ⟩ with 𝕍→WHNF 𝕍w'c ... | ƛ_ {N = N'} = let 𝕍wc = not-above-fun-𝕍{w}{Γ'}{γ₁}{N'} naf2 in ⟨ clos (ƛ N') γ₁ , ⟨ L⇓c3 , 𝕍⊔-intro 𝕍wc 𝕍w'c ⟩ ⟩ sub-𝕍 {c} {v ↦ w ⊔ v ↦ w'} ⟨ vcw , vcw' ⟩ ⊑-dist ev1c ⟨ v' , ⟨ w'' , lt ⟩ ⟩ | no naf2 | no naf3 with above-fun-⊔ ⟨ v' , ⟨ w'' , lt ⟩ ⟩ ... | inj₁ af2 = contradiction af2 naf2 ... | inj₂ af3 = contradiction af3 naf3
Case
⊑-bot
. We immediately have𝕍 ⊥ (clos (ƛ N) γ)
.Case
⊑-conj-L
.v₁' ⊑ v v₂' ⊑ v ------------------- (v₁' ⊔ v₂') ⊑ v
The induction hypotheses gives us
𝕍 v₁' (clos (ƛ N) γ)
and𝕍 v₂' (clos (ƛ N) γ)
, which is all we need for this case.Case
⊑-conj-R1
.v' ⊑ v₁ ------------- v' ⊑ (v₁ ⊔ v₂)
The induction hypothesis gives us
𝕍 v' (clos (ƛ N) γ)
.Case
⊑-conj-R2
.v' ⊑ v₂ ------------- v' ⊑ (v₁ ⊔ v₂)
Again, the induction hypothesis gives us
𝕍 v' (clos (ƛ N) γ)
.Case
⊑-trans
.v' ⊑ v₂ v₂ ⊑ v ----------------- v' ⊑ v
The induction hypothesis for
v₂ ⊑ v
gives us𝕍 v₂ (clos (ƛ N) γ)
. We apply the induction hypothesis forv' ⊑ v₂
to conclude that𝕍 v' (clos (ƛ N) γ)
.Case
⊑-dist
. This case is the most difficult. We have𝕍 (v ↦ w) (clos (ƛ N) γ) 𝕍 (v ↦ w') (clos (ƛ N) γ)
and need to show that
𝕍 (v ↦ (w ⊔ w')) (clos (ƛ N) γ)
Let
c
be an arbitrary closure such that𝔼 v c
. Assumew ⊔ w'
is greater than a function. Unfortunately, this does not mean that bothw
andw'
are above functions. But thanks to the lemmaabove-fun-⊔
, we know that at least one of them is greater than a function.Suppose both of them are greater than a function. Then we have
γ ⊢ N ⇓ clos L δ
and𝕍 w (clos L δ)
. We also haveγ ⊢ N ⇓ c₃
and𝕍 w' c₃
. Because the big-step semantics is deterministic, we havec₃ ≡ clos L δ
. Also, from𝕍 w (clos L δ)
we know thatL ≡ ƛ N'
for someN'
. We conclude that𝕍 (w ⊔ w') (clos (ƛ N') δ)
.Suppose one of them is greater than a function and the other is not: say
above-fun w
and¬ above-fun w'
. Then from𝕍 (v ↦ w) (clos (ƛ N) γ)
we haveγ ⊢ N ⇓ clos L γ₁
and𝕍 w (clos L γ₁)
. From this we haveL ≡ ƛ N'
for someN'
. Meanwhile, from¬ above-fun w'
we have𝕍 w' (clos L γ₁)
. We conclude that𝕍 (w ⊔ w') (clos (ƛ N') γ₁)
.
The proof of sub-𝔼
is direct and explained below.
sub-𝔼 {clos M γ} {v} {v'} 𝔼v v'⊑v fv' with 𝔼v (above-fun-⊑ fv' v'⊑v) ... | ⟨ c , ⟨ M⇓c , 𝕍v ⟩ ⟩ = ⟨ c , ⟨ M⇓c , sub-𝕍 𝕍v v'⊑v ⟩ ⟩
From above-fun v'
and v' ⊑ v
we have above-fun v
. Then with 𝔼 v c
we obtain a closure c
such that γ ⊢ M ⇓ c
and 𝕍 v c
. We conclude with an application of sub-𝕍
with v' ⊑ v
to show 𝕍 v' c
.
Programs with function denotation terminate via call-by-name
The main lemma proves that if a term has a denotation that is above a function, then it terminates via call-by-name. More formally, if γ ⊢ M ↓ v
and 𝔾 γ γ'
, then 𝔼 v (clos M γ')
. The proof is by induction on the derivation of γ ⊢ M ↓ v
we discuss each case below.
The following lemma, kth-x, is used in the case for the var
rule.
kth-x : ∀{Γ}{γ' : ClosEnv Γ}{x : Γ ∋ ★} → Σ[ Δ ∈ Context ] Σ[ δ ∈ ClosEnv Δ ] Σ[ M ∈ Δ ⊢ ★ ] γ' x ≡ clos M δ kth-x{γ' = γ'}{x = x} with γ' x ... | clos{Γ = Δ} M δ = ⟨ Δ , ⟨ δ , ⟨ M , refl ⟩ ⟩ ⟩
↓→𝔼 : ∀{Γ}{γ : Env Γ}{γ' : ClosEnv Γ}{M : Γ ⊢ ★ }{v} → 𝔾 γ γ' → γ ⊢ M ↓ v → 𝔼 v (clos M γ') ↓→𝔼 {Γ} {γ} {γ'} 𝔾γγ' (var{x = x}) fγx with kth-x{Γ}{γ'}{x} | 𝔾γγ'{x = x} ... | ⟨ Δ , ⟨ δ , ⟨ M' , eq ⟩ ⟩ ⟩ | 𝔾γγ'x rewrite eq with 𝔾γγ'x fγx ... | ⟨ c , ⟨ M'⇓c , 𝕍γx ⟩ ⟩ = ⟨ c , ⟨ (⇓-var eq M'⇓c) , 𝕍γx ⟩ ⟩ ↓→𝔼 {Γ} {γ} {γ'} 𝔾γγ' (↦-elim{L = L}{M = M}{v = v₁}{w = v} d₁ d₂) fv with ↓→𝔼 𝔾γγ' d₁ ⟨ v₁ , ⟨ v , ⊑-refl ⟩ ⟩ ... | ⟨ clos L' δ , ⟨ L⇓L' , 𝕍v₁↦v ⟩ ⟩ with 𝕍→WHNF 𝕍v₁↦v ... | ƛ_ {N = N} with 𝕍v₁↦v {clos M γ'} (↓→𝔼 𝔾γγ' d₂) fv ... | ⟨ c' , ⟨ N⇓c' , 𝕍v ⟩ ⟩ = ⟨ c' , ⟨ ⇓-app L⇓L' N⇓c' , 𝕍v ⟩ ⟩ ↓→𝔼 {Γ} {γ} {γ'} 𝔾γγ' (↦-intro{N = N}{v = v}{w = w} d) fv↦w = ⟨ clos (ƛ N) γ' , ⟨ ⇓-lam , E ⟩ ⟩ where E : {c : Clos} → 𝔼 v c → above-fun w → Σ[ c' ∈ Clos ] (γ' ,' c) ⊢ N ⇓ c' × 𝕍 w c' E {c} 𝔼vc fw = ↓→𝔼 (λ {x} → 𝔾-ext{Γ}{γ}{γ'} 𝔾γγ' 𝔼vc {x}) d fw ↓→𝔼 𝔾γγ' ⊥-intro f⊥ = contradiction f⊥ above-fun⊥ ↓→𝔼 𝔾γγ' (⊔-intro{v = v₁}{w = v₂} d₁ d₂) fv12 with above-fun? v₁ | above-fun? v₂ ... | yes fv1 | yes fv2 with ↓→𝔼 𝔾γγ' d₁ fv1 | ↓→𝔼 𝔾γγ' d₂ fv2 ... | ⟨ c₁ , ⟨ M⇓c₁ , 𝕍v₁ ⟩ ⟩ | ⟨ c₂ , ⟨ M⇓c₂ , 𝕍v₂ ⟩ ⟩ rewrite ⇓-determ M⇓c₂ M⇓c₁ = ⟨ c₁ , ⟨ M⇓c₁ , 𝕍⊔-intro 𝕍v₁ 𝕍v₂ ⟩ ⟩ ↓→𝔼 𝔾γγ' (⊔-intro{v = v₁}{w = v₂} d₁ d₂) fv12 | yes fv1 | no nfv2 with ↓→𝔼 𝔾γγ' d₁ fv1 ... | ⟨ clos {Γ'} M' γ₁ , ⟨ M⇓c₁ , 𝕍v₁ ⟩ ⟩ with 𝕍→WHNF 𝕍v₁ ... | ƛ_ {N = N} = let 𝕍v₂ = not-above-fun-𝕍{v₂}{Γ'}{γ₁}{N} nfv2 in ⟨ clos (ƛ N) γ₁ , ⟨ M⇓c₁ , 𝕍⊔-intro 𝕍v₁ 𝕍v₂ ⟩ ⟩ ↓→𝔼 𝔾γγ' (⊔-intro{v = v₁}{w = v₂} d₁ d₂) fv12 | no nfv1 | yes fv2 with ↓→𝔼 𝔾γγ' d₂ fv2 ... | ⟨ clos {Γ'} M' γ₁ , ⟨ M'⇓c₂ , 𝕍2c ⟩ ⟩ with 𝕍→WHNF 𝕍2c ... | ƛ_ {N = N} = let 𝕍1c = not-above-fun-𝕍{v₁}{Γ'}{γ₁}{N} nfv1 in ⟨ clos (ƛ N) γ₁ , ⟨ M'⇓c₂ , 𝕍⊔-intro 𝕍1c 𝕍2c ⟩ ⟩ ↓→𝔼 𝔾γγ' (⊔-intro d₁ d₂) fv12 | no nfv1 | no nfv2 with above-fun-⊔ fv12 ... | inj₁ fv1 = contradiction fv1 nfv1 ... | inj₂ fv2 = contradiction fv2 nfv2 ↓→𝔼 {Γ} {γ} {γ'} {M} {v'} 𝔾γγ' (sub{v = v} d v'⊑v) fv' with ↓→𝔼 {Γ} {γ} {γ'} {M} 𝔾γγ' d (above-fun-⊑ fv' v'⊑v) ... | ⟨ c , ⟨ M⇓c , 𝕍v ⟩ ⟩ = ⟨ c , ⟨ M⇓c , sub-𝕍 𝕍v v'⊑v ⟩ ⟩
Case
var
. Looking upx
inγ'
yields some closure,clos M' δ
, and from𝔾 γ γ'
we have𝔼 (γ x) (clos M' δ)
. With the premiseabove-fun (γ x)
, we obtain a closurec
such thatδ ⊢ M' ⇓ c
and𝕍 (γ x) c
. To concludeγ' ⊢ x ⇓ c
via⇓-var
, we needγ' x ≡ clos M' δ
, which is obvious, but it requires some Agda shananigans via thekth-x
lemma to get our hands on it.Case
↦-elim
. We haveγ ⊢ L · M ↓ v
. The induction hypothesis forγ ⊢ L ↓ v₁ ↦ v
gives usγ' ⊢ L ⇓ clos L' δ
and𝕍 v (clos L' δ)
. Of course,L' ≡ ƛ N
for someN
. By the induction hypothesis forγ ⊢ M ↓ v₁
, we have𝔼 v₁ (clos M γ')
. Together with the premiseabove-fun v
and𝕍 v (clos L' δ)
, we obtain a closurec'
such thatδ ⊢ N ⇓ c'
and𝕍 v c'
. We conclude thatγ' ⊢ L · M ⇓ c'
by rule⇓-app
.Case
↦-intro
. We haveγ ⊢ ƛ N ↓ v ↦ w
. We immediately haveγ' ⊢ ƛ M ⇓ clos (ƛ M) γ'
by rule⇓-lam
. But we also need to prove𝕍 (v ↦ w) (clos (ƛ N) γ')
. Letc
by an arbitrary closure such that𝔼 v c
. Supposev'
is greater than a function value. We need to show thatγ' , c ⊢ N ⇓ c'
and𝕍 v' c'
for somec'
. We prove this by the induction hypothesis forγ , v ⊢ N ↓ v'
but we must first show that𝔾 (γ , v) (γ' , c)
. We prove that by the lemma𝔾-ext
, using facts𝔾 γ γ'
and𝔼 v c
.Case
⊥-intro
. We have the premiseabove-fun ⊥
, but that’s impossible.Case
⊔-intro
. We haveγ ⊢ M ↓ (v₁ ⊔ v₂)
andabove-fun (v₁ ⊔ v₂)
and need to showγ' ⊢ M ↓ c
and𝕍 (v₁ ⊔ v₂) c
for somec
. Again, byabove-fun-⊔
, at least one ofv₁
orv₂
is greater than a function.Suppose both
v₁
andv₂
are greater than a function value. By the induction hypotheses forγ ⊢ M ↓ v₁
andγ ⊢ M ↓ v₂
we haveγ' ⊢ M ⇓ c₁
,𝕍 v₁ c₁
,γ' ⊢ M ⇓ c₂
, and𝕍 v₂ c₂
for somec₁
andc₂
. Because⇓
is deterministic, we havec₂ ≡ c₁
. Then by𝕍⊔-intro
we conclude that𝕍 (v₁ ⊔ v₂) c₁
.Without loss of generality, suppose
v₁
is greater than a function value butv₂
is not. By the induction hypotheses forγ ⊢ M ↓ v₁
, and using𝕍→WHNF
, we haveγ' ⊢ M ⇓ clos (ƛ N) γ₁
and𝕍 v₁ (clos (ƛ N) γ₁)
. Then becausev₂
is not greater than a function, we also have𝕍 v₂ (clos (ƛ N) γ₁)
. We conclude that𝕍 (v₁ ⊔ v₂) (clos (ƛ N) γ₁)
.
Case
sub
. We haveγ ⊢ M ↓ v
,v' ⊑ v
, andabove-fun v'
. We need to show thatγ' ⊢ M ⇓ c
and𝕍 v' c
for somec
. We haveabove-fun v
byabove-fun-⊑
, so the induction hypothesis forγ ⊢ M ↓ v
gives us a closurec
such thatγ' ⊢ M ⇓ c
and𝕍 v c
. We conclude that𝕍 v' c
bysub-𝕍
.
Proof of denotational adequacy
From the main lemma we can directly show that ℰ M ≃ ℰ (ƛ N)
implies that M
big-steps to a lambda, i.e., ∅ ⊢ M ⇓ clos (ƛ N′) γ
.
↓→⇓ : ∀{M : ∅ ⊢ ★}{N : ∅ , ★ ⊢ ★} → ℰ M ≃ ℰ (ƛ N) → Σ[ Γ ∈ Context ] Σ[ N′ ∈ (Γ , ★ ⊢ ★) ] Σ[ γ ∈ ClosEnv Γ ] ∅' ⊢ M ⇓ clos (ƛ N′) γ ↓→⇓{M}{N} eq with ↓→𝔼 𝔾-∅ ((proj₂ (eq `∅ (⊥ ↦ ⊥))) (↦-intro ⊥-intro)) ⟨ ⊥ , ⟨ ⊥ , ⊑-refl ⟩ ⟩ ... | ⟨ clos {Γ} M′ γ , ⟨ M⇓c , Vc ⟩ ⟩ with 𝕍→WHNF Vc ... | ƛ_ {N = N′} = ⟨ Γ , ⟨ N′ , ⟨ γ , M⇓c ⟩ ⟩ ⟩
The proof goes as follows. We derive ∅ ⊢ ƛ N ↓ ⊥ ↦ ⊥
and then ℰ M ≃ ℰ (ƛ N)
gives us ∅ ⊢ M ↓ ⊥ ↦ ⊥
. We conclude by applying the main lemma to obtain ∅ ⊢ M ⇓ clos (ƛ N′) γ
for some N′
and γ
.
Now to prove the adequacy property. We apply the above lemma to obtain ∅ ⊢ M ⇓ clos (ƛ N′) γ
and then apply cbn→reduce
to conclude.
adequacy : ∀{M : ∅ ⊢ ★}{N : ∅ , ★ ⊢ ★} → ℰ M ≃ ℰ (ƛ N) → Σ[ N′ ∈ (∅ , ★ ⊢ ★) ] (M —↠ ƛ N′) adequacy{M}{N} eq with ↓→⇓ eq ... | ⟨ Γ , ⟨ N′ , ⟨ γ , M⇓ ⟩ ⟩ ⟩ = cbn→reduce M⇓
Call-by-name is equivalent to beta reduction
As promised, we return to the question of whether call-by-name evaluation is equivalent to beta reduction. In chapter BigStep we established the forward direction: that if call-by-name produces a result, then the program beta reduces to a lambda abstraction (cbn→reduce
). We now prove the backward direction of the if-and-only-if, leveraging our results about the denotational semantics.
reduce→cbn : ∀ {M : ∅ ⊢ ★} {N : ∅ , ★ ⊢ ★} → M —↠ ƛ N → Σ[ Δ ∈ Context ] Σ[ N′ ∈ Δ , ★ ⊢ ★ ] Σ[ δ ∈ ClosEnv Δ ] ∅' ⊢ M ⇓ clos (ƛ N′) δ reduce→cbn M—↠ƛN = ↓→⇓ (soundness M—↠ƛN)
Suppose M —↠ ƛ N
. Soundness of the denotational semantics gives us ℰ M ≃ ℰ (ƛ N)
. Then by ↓→⇓
we conclude that ∅' ⊢ M ⇓ clos (ƛ N′) δ
for some N′
and δ
.
Putting the two directions of the if-and-only-if together, we establish that call-by-name evaluation is equivalent to beta reduction in the following sense.
cbn↔reduce : ∀ {M : ∅ ⊢ ★} → (Σ[ N ∈ ∅ , ★ ⊢ ★ ] (M —↠ ƛ N)) iff (Σ[ Δ ∈ Context ] Σ[ N′ ∈ Δ , ★ ⊢ ★ ] Σ[ δ ∈ ClosEnv Δ ] ∅' ⊢ M ⇓ clos (ƛ N′) δ) cbn↔reduce {M} = ⟨ (λ x → reduce→cbn (proj₂ x)) , (λ x → cbn→reduce (proj₂ (proj₂ (proj₂ x)))) ⟩
Unicode
This chapter uses the following unicode:
𝔼 U+1D53C MATHEMATICAL DOUBLE-STRUCK CAPITAL E (\bE)
𝔾 U+1D53E MATHEMATICAL DOUBLE-STRUCK CAPITAL G (\bG)
𝕍 U+1D53E MATHEMATICAL DOUBLE-STRUCK CAPITAL V (\bV)